Association between Respiratory Virus Infection and Development of De Novo Donor-Specific Antibody in Lung Transplant Recipients - Anoma Nellore; Julie Houp; John T. Killian; Ajit P. Limaye; Cynthia E. Fisher (Viruses, 2024)
Chronic lung allograft dysfunction (CLAD) is the most common cause of long-term lung allograft failure. Several factors, including respiratory virus infection (RVI), have been associated with CLAD development, but the underlying mechanisms of these associations are not well understood. We hypothesize that RVI in lung transplant recipients elicits the development of donor-specific antibodies (DSAs), thus providing a mechanistic link between RVI and CLAD development. To test this hypothesis, we retrospectively evaluated for the presence of HLA antibodies in a cohort of lung transplant recipients with symptomatic RVI within the first four months post-transplant using sera at two time points (at/directly after the transplant and following RVI) and time-matched controls without RVI (post-transplant). We found a trend toward the development of de novo DSAs in those with symptomatic RVI versus controls [6/21 (29%) vs. 1/21 (5%), respectively, p = 0.09]. No cases or controls had DSA at baseline. We also found increased rates of CLAD and death among those who developed class II DSA versus those who did not (CLAD: 5/7 (71.4%) vs. 19/34 (54.3%), death: 5/7 (71.4%) vs. 17/35 (48.6%)). Prospective studies evaluating the temporal development of DSA after RVI in lung transplant patients and the subsequent outcomes are warranted.